Surface polarity control in ZnO films deposited by pulsed laser deposition - Luo, Cai-Qin; Ling, Francis Chi-Chung; Rahman, M. Azizar; Phillips, Matthew; Ton-That, Cuong; Liao, Changzhong; Shih, Kaimin; Lin, Jingyang; Tam, Ho Won; Djurišić, Aleksandra B.; Wang, Shuang-Peng (Applied surface science, 2019)
We demonstrate a simple and inexpensive method of surface polarity control of ZnO grown by pulsed laser deposition (PLD). The polarity control is achieved in a straightforward way by changing the thickness of MgO buffer layer. The Zn- and O-polar ZnO films possess very distinct growth rate, electron concentration and mobility as well as different defect structures. These different structural and electronic properties result in significant differences in surface reactivity and device performance. For example, Pd Schottky diodes fabricated onto the O-polar ZnO film exhibit lower barrier height and ideality factor compared with the equivalent Zn-polar devices, while methylammonium lead iodide perovskite films are readily formed on O-terminated and rapidly decompose on Zn-terminated surfaces. This can be attributed to higher photocatalytic activity of Zn-terminated surface, as well as higher surface coverage of adsorbed hydroxyl groups. Consequently, our results indicate that polarity engineering to obtain favorable O-terminated surface can result in improved performance of ZnO-containing optoelectronic devices, while Zn-terminated surfaces could be of interest for photocatalytic and sensing applications. •ZnO polarity control achieved in PLD growth.•Surface absorption, electrical and optical properties of are highly polarity dependent.•Photocatalytic activity is enhanced and MAPI perovskite film decompose on Zn-polar surface.